The Covid-19 Epidemic in Serbia – the Challenges of Finding an Appropriate Basis for Responding to a Health Crisis - Nikolić Popadić, Sofija; Milenković, Marko; Sjeničić, Marta (Medicine, Law & Society, 2021)
Abstract The World Health Organization declared the Covid-19 pandemic on 11 March, 2020. Serbia declared a State of Emergency (SoE) on 15 March, just days after the country’s first official case, part of an unprecedented global wave of emergency responses, with states reacting differently to the threat of the virus. Decision makers in Serbia opted to declare a SoE, followed by a series of governmental decrees and ministerial orders. This paper examines the Serbian government’s initial response. The legislation in force in March 2020 is analysed to explore what possibilities and instruments could have been used, with particular focus on legislation regarding infectious diseases and disaster responses, which allowed for the declaration of an emergency situation, and the introduction of legitimate restrictions to fight the outbreak. The paper concludes that the full potential of all available measures and instruments was not exhausted, especially regarding legislation relating to an emergency situation.